Understanding and Managing Gill Infections in Fish - Nawar; Abbas Dakheel, Mutar; Zainab Dakhil Degaim (University of Thi-Qar Journal of agricultural research, 2024)
Gill diseases, including those associated with gill infections, are some of the most common and severe health issues in farmed and wild fish. The occurrence of disease in the same location can result in fish from different phylogenetic groups presenting with similar pathological changes, suggesting that the disease is likely multifactorial. Gill diseases are therefore usually the result of complex interactions between the infectious agent, the host, and the environment. While gill diseases are often associated with microbial infections, they can also be exacerbated by environmental stress without microbial involvement. Indeed, primary gill infections are rare in fish, while an immune response detected in gill tissue of affected animals is common. This suggests that the environment plays a significant role in gill disease outbreaks. The aim of this review is to contribute towards a better understanding of the factors associated with gill infections in fish, as this is an important step in the management of gill diseases. In wild and farmed fish, gill diseases are some of the most common and severe health issues. These diseases are often associated with microbial infections and can be exacerbated by environmental stress. Loss of osmoregulatory function, mechanical damage, and hypoxia are among the harmful effects these diseases have on fish gills. Therefore, managing gill diseases is an important aspect of fish health management. To do this, we need to develop an understanding of the factors that influence gill disease outbreaks, including how the composition of the gill microbiome changes and what effect the wider aquatic microbiome has on gill health. This knowledge can then be used to develop preventative measures or treatments that help to mitigate gill disease in affected animals.